Humble Leadership Affects Organizational Citizenship Behavior: The Sequential Mediating Effect of Strengths Use and Job Crafting - Ding, He; Yu, Enhai; Chu, Xixi; Li, Yanbin; Amin, Kashif (Frontiers in Psychology, 2020)
The purpose of the current study is to investigate the impact of humble leadership on organizational citizenship behavior (OCB) and the sequential mediation effect of strengths use and job crafting on the relationship. Data were collected at two points in time, spaced by a 2-week interval, with a sample of 260 employees working in a hospital in Beijing, China. Structural equation modeling was applied to test our predictions. The results indicated that humble leadership is positively related to OCB; the relationship between humble leadership and OCB was mediated not only by job crafting but also by strengths use and job crafting (sequential mediation). However, the indirect effect of humble leadership on OCB through the mechanism of strengths use was not statistically significant. This study advances the theory and research on the leadership–OCB relationship.